EFEKTIVITAS PROGRAM KELUARGA HARAPAN (PKH) DALAM MENINGKATKAN SOSIAL EKONOMI MASYARAKAT DESA - Roki Gentara; Rosyidah Rachman; S Suprianto (Jurnal Ekonomi & Bisnis, 2023)
This research aims to determine the effectiveness of the Family Hope Program (PKH) in improving the socio-economic status of the Baturotok Village community. This research is descriptive with a quantitative approach. The type of data used in this research is quantitative data in the form of respondents' answer scores obtained directly from primary sources using a questionnaire as a data collection instrument. In this research, the sample chosen was 10% of the total beneficiaries of the Family Hope Program (PKH) in Baturotok Village, totaling 345 heads of families, so the respondents were 35 heads of families. Measuring the level of program effectiveness uses simple statistical methods, and classifying the level of program effectiveness can be done using standards in accordance with the Ministry of Home Affairs' R&D reference. The results of this research indicate that the level of effectiveness of the PKH program in improving the socio-economic status of the Baturotok Village community is in the quite effective category. This means that the implementation of the PKH program in Baturotok Village has been carried out quite well, although improvements and enhancements are still needed in several aspects, namely socialization activities and monitoring of the PKH program. Success in implementing the PKH program is very important so that poor people can gain benefits, especially access to education, health and social sectors so that the goal of the PKH program in improving the socio-economic status of the community can be achieved optimally.